FTIR characteristics of sweet flour as affected by particle size distribution and in vitro digestibility of gluten-free sweet potato noodles - Muhammad Azeem; Syed Abdul Wadood; Tahir Mahmood Qureshi; Muhammad Anees Ur Rehman; Isam A. Mohamed Ahmed; Moneera O. Aljobair; Asmahan A. Ali (International Journal of Food Properties)
There is a need to explore the influence of particle size of sweet potato flour on physicochemical properties and in vitro starch digestibility of gluten free sweet potato noodles. The aim of this work was to examine the influence of purple-fleshed sweet potato flour (PFSPF) having different particle size distribution (355 µm to 75 µm) on physicochemical properties and in vitro starch digestibility of gluten-free purple sweet potato noodles. Pasting properties and sugar contents were positively correlated toward the finest particle fraction. The hardness of noodles was positively and significantly correlated to the finest particle size fraction. Sweet potato flour (SPF) noodles prepared with particle size of 75 µm retained lower hardness 5.74 N. An abrupt increase in yellowness was observed with decreasing particle size that might be attributed to the reduction of protein. The results of FTIR suggested that with the reduction of particle size, protein and carbohydrates decreased that much associated with crystallization and retrogradation of starch. Among all the amino acids, aspartic acid and glutamic acid were observed to be more abundant, i.e. approximately 13.33 and 29.05%, respectively. In this way, PFSPF with particle size 75 µm exhibited significant application potential for producing gluten free noodles due to high resistant starch and lower hardness. It may be concluded that particle sizes of sweet potato flour influenced pasting properties, textural characteristics, sugar contents, protein contents, amino acid contents, carbohydrate contents of prepared noodles.